A Qualitative Study of Harnessing Entrepreneurial Leadership for Sustainable Growth - Renaldo, Nicholas; Suhardjo, Suhardjo; Musa, Sulaiman; Cecilia, Cecilia; Veronica, Kristy (First Ciera Publisher, 2024)
The primary aim of this qualitative study is to explore the mechanisms through which entrepreneurial leadership can be leveraged to promote sustainable growth within organizations. This study contributes to the existing literature in several novel ways: Focused Qualitative Inquiry, Contextualized Exploration, Practical Implications, and Development of variable dimensions and indicators. Given the exploratory nature of the research questions and the need to understand complex phenomena in-depth, a qualitative research design is adopted. Organizations are selected purposively based on their reputation for entrepreneurial leadership and commitment to sustainability. Qualitative data from interviews, focus groups, and document analysis are analyzed thematically to identify recurring patterns, themes, and categories related to entrepreneurial leadership and sustainability (Thematic Analysis). The findings underscore the importance of visionary leadership, strategic alignment, and stakeholder engagement in advancing sustainability goals and fostering resilience in the face of evolving challenges. By leveraging their creativity, resilience, and strategic acumen, entrepreneurial leaders can navigate complex sustainability landscapes, driving innovation, and value creation while balancing competing priorities and stakeholder interests.